A Randomized Controlled Study of Silver-Based Burns Dressing in a Pediatric Emergency Department. Issue 4 (July 2016) - Brown, Matthew; Dalziel, Stuart R.; Herd, Eleanor; Johnson, Kathryn; Wong She, Richard; Shepherd, Michael
Abstract : Silver-impregnated dressings are increasingly preferred over silver sulfadiazine cream in the management of pediatric burns. An ideal burns dressing would provide a moist, sterile environment, discourage infection, and not require painful dressing changes. This study sought to determine whether silver sodium carboxymethyl cellulose (Aquacel ® Ag, ConvaTec, Greensboro, NC) dressing is a superior treatment to nanocrystalline silver-coated polyethylene (Acticoat ™, Smith & Nephew, London, United Kingdom) dressing in pediatric patients with partial thickness burns. The authors conducted a single-blind, randomized controlled trial in 89 patients presenting to Starship Children's Emergency Department with uncomplicated partial-thickness burns. Patients were randomized to receive either an Acticoat ™ (n = 45) or Aquacel ® Ag (n = 44) dressing. Photographs of the burn before dressing and at day 10 were assessed by two blinded pediatric burn surgeons to determine the primary outcome and percentage epithelialization. Secondary outcomes were number of dressing changes required and number and type of adverse events. Both treatment groups achieved satisfactory rates of burn healing. There was no difference between groups in the percentage epithelialization at day 10 (Acticoat ™ [mean ± SD] = 93 ± 14%; Aquacel ® Ag = 94 ± 17%, P = .89). Adverse events such as infection and escalation of care were rare, with no difference detected between groups. Compared with Acticoat ™, Aquacel ® Ag dressings required significantly less dressing changes per patient {Acticoat ™ [median (interquartile range)] = 2 (2–2), Aquacel ® Ag=1 (1–1), P = .03}. Both Acticoat ™ and Aquacel ® Ag dressings are effective burn dressings, allowing reepithelialization and preventing infection in a subset of uncomplicated partial-thickness burns in pediatric patients. Aquacel ® Ag requires fewer dressing changes. This decrease in frequency of dressing changes and direct manipulation of the wound, which can be distressing or require additional intervention, identified Aquacel ® Ag as the superior dressing. The majority of partial thickness pediatric burns heal within 10 days; however, a considerable minority requires the wound to be dressed for a longer period of time and/or specialist intervention. To identify these patients, expert review of the wound at 10 days postburn is recommended.